EKSISTENSI PEDAGANG PASAR TRADISIONAL DALAM MENINGKATKAN PEREKONOMIAN PEDAGANG PASAR TARUTUNG 2024 - Bawamenewi, Diani; Sitorus, Masniar Hernawati; Sitindaon, Wensdy; Panjaitan, Ade Putera Arif; Firmando, Harisan Boni (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
The objectives of this study are 1). To find out the existence of traditional market traders in improving the economy of Tarutung market traders. 2). To find out the strategy of traditional market traders in improving the economy of Tarutung market traders. 3). To find out the challenges of traders in the competition of traders in the Tarutung market. This type of research uses a qualitative approach with a descriptive approach or a type of field research. The results of this study can be concluded that: The income of traders in the Tarutung traditional market has increased, and provides benefits for the economy of traders, where in the Tarutung market every year the traders and visitors are also getting more crowded, this is a factor in increasing the increase in the income of traders in the Tarutung market and can survive. The challenges faced by traders in the Tarutung market in trader competition are the number of traders who sell similar products or merchandise so that they experience tight competition, price competition because in the Tarutung market there are still the same prices and competition between the modern market and the traditional market.